(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The aim of this paper was to assess the toxicological impacts of the Herbicide 2, 4-D Dimethyl amine salt on Clarias gariepinus fingerlings. The fishes were exposed to lethal concentration of 0.00, 1.34, 1.42, 1.48, 1.54 and 1.60ml/L for 96 hours as well as sub-lethal concentrations of 0.00, 0.069, 0.138 and 0.276ml/l of 2, 4-D Dimethyl amine salt for 8 weeks. The value of 96 hours LC50 was 1.385ml/L. Respiratory disturbance, loss of equilibrium, and sudden fish death were observed in 96hrs of exposed fish, and these varied greatly with increase in concentration of the toxicant, with a trend of significant (p<0.05) increase in mortality with increasing concentrations. As the concentration of 2, 4-D dimethyl amine salt increased the beats of the tail and opercular ventilation increased at 12 and 24 but decreased at 72 and 96 hours. The lethal exposure of Clarias gariepinus fingerlings to 2, 4-D dimethyl amine salt indicate significant changes in enzymes activity of liver for SOD and CAT. at 1.36, 1.42, 1.48, 1.54 and 1.6ml/L while sub-lethal show no significant changes. The changes for lethal and sub-lethal in gills were characterized by, inflammation of primary and secondary lamella, vacuolation, filament atropy. The liver showed, necrosis, adipocyte infiltration, and lymphocyte hyperplasia in fish exposed lethal and sub lethal concentrations of 2, 4-D Dimethyl amine salt.